Averaging of Oscillation Systems with Delay and Integral Boundary Conditions - Bigun, Ya. I. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We prove the existence of a solution and obtain an estimate for the error of the averaging method for a multifrequency system with linearly transformed argument and integral boundary conditions.